Evaluation of Acceptance Model in E-Commerce Using TAM - Calvin Kumajas, Dwiputri Pusung, Michella Undap (International Journal of Information Technology and Education, 2021)
Information technology has had an impact on human life, including business on the internet, namely E-Commerce which saves time and does not require large capital to promote products. and encouragement to make changes in the system so that technology acceptance increases and they can take advantage of it. This study uses the TAM method as a reference to evaluate the level of technology acceptance in e-commerce systems by system users or the whole community. The results of this study indicate that the majority of E-Commerce System users agree that this E-Commerce system helps them. The results of this study also show that e-commerce must pay attention to interest, perceived usefulness, perception and ease of use in implementing and developing e-commerce-based information systems.